Estimating the Impact of Improved Roads on Access to Health Care : Evidence from Mozambique - Iimi, Atsushi (World Bank, Washington, DC, 2021)
The paper recasts light on the linkage between transport infrastructure and human capital development. Health care access is an important challenge in many developing countries. In particular in remote rural areas, it is not easy to access good quality health care services. Among others, transport connectivity is often an important constraint. The paper estimates the impact of transport connectivity on access to health care services in Mozambique, especially focused on people’s decision about whether they visit and ask for advice at a health facility if they have a fever. This is a critical question in Mozambique where malaria is still a life-threatening disease. About three-quarters of the total population does not have access to health facilities by walking. The paper shows that transport connectivity to health facilities is a significant determinant of people’s health care access. Owning transport means, such as a bike or a motorcycle, is also instrumental to promoting people’s access to health care. The rich are more likely to benefit from health care services, suggesting a need for other complementary policies, such as a health care subsidy and insurance, to improve health care accessibility.